Obesity retunes turnover kinetics of tissue-resident macrophages in fat - Chen, Qi (2022)
Adipose tissue-resident F4/80hi macrophages (ATMs) are the main leukocyte population found in the visceral adipose tissue (VAT). These macrophages comprise several phenotypically distinct subpopulations that rapidly shift in abundance during obesity-induced tissue remodeling. Here we used a fate-mapping approach in mouse models to determine the developmental origins and the differential turnover kinetics of ATMs in lean and obese adipose tissue. We found that in lean, murine VAT the majority of ATMs express T cell immunoglobulin and mucin domain containing 4 receptor (Tim-4), lack the expression of CCR2 and can be further subdivided based on their expression of MHC class II and CD11c. We showed that both embryonic-derived Tim-4+ MHCIIlow and Tim-4+ MHCII+ ATM subsets are long-lived and only slowly replenished by monocytes over time. Only a minor Tim-4- MHCII+ CD11c+ ATM fraction expresses CCR2 and is short-lived. In response to high-fat induced VAT remodeling, the majority of Tim-4+ MHCIIlow ATMs maintain their fetal identity as they are moderately displaced by monocytes. Conversely, Tim-4+ MHCII+ ATMs are quickly replaced in a CCR2-dependent manner by bone marrow-derived Tim-4- MHCII+ ATMs that have significantly higher turnover rates than those in lean mice. In addition, during high-fat diet, the subpopulation of CD11c+ macrophages invade the VAT with the fastest turnover kinetics of all three ATM subpopulations. Our results suggest that ATM subpopulation frequency is controlled by the VAT microenvironment and that obesity-induced tissue remodeling renders some of the ATM niches accessible and available for rapid monocyte replenishment. Specialized monocyte-derived macrophages, which are rapidly recruited may be contributing to control the excess of adipocyte-released lipids produced during obesity.